A Study of Pile Displacement in Soft Soil: The Case of Semarang - Demak Toll Road Construction Package 1B - Sagita, Novera; Wahyudi, Herman; Lastiasih, Yudhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
In the construction package of Semarang-Demak Toll Road 1B, an elevated bridge is planned to be built using a pile foundation of 56 pieces with a diameter of 1.0 m installed at a depth of 68m. The soil conditions at the site are very soft to medium clay and silt. During the excavation of the footing work, there was a displacement of 11 piles. This study aims to analyze the pile displacement behavior at each work sequence due to the influence of excess pore pressure and excavator distance near the pile. The pile displacement behavior was modeled using a Finite Element Method (FEM) based program, Plaxis 2D. Piles are modeled using an elastic constitution model to obtain deformation results that match the actual conditions in the field. While the soil is modeled using the Mohr Coulomb soil constitutive model on the embankment soil and Soft Soil on the original soil. The analysis was conducted to determine the lateral displacement of poles in field conditions at each sequence of work on unconsolidated soil with/without an excavator load of 15 kN. The results showed that by conditioning the soil at 90% consolidation degree (U90%) can reduce the lateral displacement value of the pile by 95.96% at the 4 m deep excavation stage compared to the unconsolidated soil. By placing the excavator 6.5 m away from the piles, it can reduce the lateral displacement that occurs by 20.96% compared to the existing position of 3.5 m from the piles.